Materials handling handbook - Mulcahy, David E. (McGraw-Hill handbooks., 1999)
Introduces you to the methods for designing, organizing, operating, and maintaining materials handling/product movement system. This book helps you learn about horizontal and vertical transportation techniques for items of all sizes, and get full details on: inventory control; identification systems; cost estimates; site selection; and security.